2020
DOI: 10.1039/c9ee03250a
|View full text |Cite|
|
Sign up to set email alerts
|

Self-assembled Ti3C2 MXene and N-rich porous carbon hybrids as superior anodes for high-performance potassium-ion batteries

Abstract: The novel PDDA-NPCNs/Ti3C2 hybrids via an electrostatic attraction self-assembly approach effectively accelerate reaction kinetics and improve electrochemical performance as PIBs anodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
201
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 294 publications
(219 citation statements)
references
References 67 publications
8
201
0
Order By: Relevance
“…MXenes are a group of 2D transition metal carbide and/or carbonitrides with excellent electrical conductivity, hydrophilic surface and mechanical stability, which are used in various fields, such as electromagnetic interference shield (EMI), [ 1 ] batteries, [ 2 ] sensors, [ 3 ] catalysis, [ 4 ] and supercapacitors. [ 5 ] The typical representative of MXene is Ti 3 C 2 T x , T x represents –OH, –F, –O on the surface of MXene.…”
Section: Methodsmentioning
confidence: 99%
“…MXenes are a group of 2D transition metal carbide and/or carbonitrides with excellent electrical conductivity, hydrophilic surface and mechanical stability, which are used in various fields, such as electromagnetic interference shield (EMI), [ 1 ] batteries, [ 2 ] sensors, [ 3 ] catalysis, [ 4 ] and supercapacitors. [ 5 ] The typical representative of MXene is Ti 3 C 2 T x , T x represents –OH, –F, –O on the surface of MXene.…”
Section: Methodsmentioning
confidence: 99%
“…Because of high electric conductivity, suitable viscosity, and good film-forming property, MXene is considered as an ideal conductive substrate, binder, or current collector to construct the hybrids for PIBs. [91,107] For instance, N-rich porous carbon nanosheets (NPCNs) with high doping level (10.35 at%) were first modified with PDDA (Figure 9a,b), [48] giving birth to positively charged PDDA-NPCN. Then, electrostatic selfassembly of PDDA-NPCN and exfoliated negatively charged Ti 3 C 2 nanosheets (ex-Ti 3 C 2 ) was carried out to form the tight anchoring of PDDA-NPCN nanosheets on the surface of MXene nanosheets (Figure 9c).…”
Section: Mxene-based Hybrid Electrodesmentioning
confidence: 99%
“…In this study, rGO modified by poly(diallyldimethylammonium chloride) (PDDA) with a positive zeta potential enables the self‐assembly of rGO and MXene layer‐by‐layer by electrostatic interaction, resulting in a well‐aligned structure and increased interlayer spacing, which accounts for its excellent electrochemical performance ( Figure a,b). Additionally, Zhao et al have demonstrated the self‐assembly of positively charged N‐rich porous carbon nanosheets modified by PDDA and negatively charged MXene nanosheets with an enlarged interlayer spacing and unique 3D interconnected networks 80…”
Section: The Mxene Assembliesmentioning
confidence: 99%